Critical Discourse Analysis of Positive Narratives About Prabowo Subianto in YouTube Video of Helmy Yahya Berbicara - Widianti, Dwi; Sufyanto, Sufyanto (Procedia of Social Sciences and Humanities, 2024)
This study analyzes Helmy Yahya's video entitled "Learning from Prabowo's Victory" using Van Dijk's discourse analysis approach, which involves macrostructures, superstructures, and microstructures. The purpose of this research is to understand how Helmy Yahya builds a positive narrative about Prabowo Subianto and how the discourse affects public perception. The results of the study show that Helmy Yahya effectively utilizes the macro structure to set a big theme in the form of a positive image of Prabowo as an ideal leader. The superstructure is used to compose a narrative logically and systematically, starting with an introduction to the political context, a detailed discussion of Prabowo's advantages, to a conclusion that strengthens the image. Microstructure, through the use of persuasive language and positive terms, serves to strengthen the narrative and influence the opinion of the audience. The discourse built in this video has the potential to affect public perception, especially among voters who are still hesitant or uninformed. By highlighting Prabowo's strengths and using an effective rhetorical strategy, Helmy Yahya succeeded in forming public opinion that is more supportive of Prabowo as an candidate for Indonesia's leader.